2000
DOI: 10.1038/35016020
|View full text |Cite
|
Sign up to set email alerts
|

Hidden symmetries in the energy levels of excitonic ‘artificial atoms’

Abstract: Quantum dots or 'artificial atoms' are of fundamental and technological interest--for example, quantum dots may form the basis of new generations of lasers. The emission in quantum-dot lasers originates from the recombination of excitonic complexes, so it is important to understand the dot's internal electronic structure (and of fundamental interest to compare this to real atomic structure). Here we investigate artificial electronic structure by injecting optically a controlled number of electrons and holes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
277
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 419 publications
(296 citation statements)
references
References 24 publications
14
277
1
4
Order By: Relevance
“…When a laser pulse optically creates several electron-hole pairs in a QD, the system goes back to its ground state by emitting a cascade of photons. Thanks to the strong Coulomb interaction, only a single photon is emitted for a given emission energy 11 . This property has been exploited to generate single photons 6 , as well as single entangled photon pairs 12,13 .…”
mentioning
confidence: 99%
“…When a laser pulse optically creates several electron-hole pairs in a QD, the system goes back to its ground state by emitting a cascade of photons. Thanks to the strong Coulomb interaction, only a single photon is emitted for a given emission energy 11 . This property has been exploited to generate single photons 6 , as well as single entangled photon pairs 12,13 .…”
mentioning
confidence: 99%
“…These states have been observed in previous studies performed on single InAs QDs grown by the SK method. 25,27 It has been suggested that these states arise from interaction between the band-filled wetting layer and the state-filled QD. 44 A precise analysis of the power dependence of PL intensity from the states other than s-shell states was complicated by the emergence of new peaks and the spectral broadening.…”
mentioning
confidence: 99%
“…This model can be justified by the (395) shell structure observed when a quantum dot is filled either with excitons [1] or with electrons [2]. At low temperature, the artificial atom picture is strengthened by the long coherence times of an exciton in a quantum dot [3][4][5], motivating the application of quantum dots in quantum optics and quantum information processing.…”
Section: Introductionmentioning
confidence: 99%